Curricular training report at the UFS and the INFARMED, I.P - Bernardino, Alexandra Filipa Carocinho (2014)
The present report describes my 9 months experience as a trainee at the Southern Pharmacovigilance Unit, a Regional Pharmacovigilance Unit of the National Pharmacovigilance System and at the Risk Management for Medicines Department of the National Authority of Medicines and Health Products, I.P.. The main objective of this training was the acquisition of technical skills and experience in pharmacovigilance and the consolidation of some knowledge acquired during my Degree in Biomedical Sciences and my first year of the Master’s Degree in Pharmaceutical Biomedicine. The activities developed focused mostly on the processing of spontaneous reports of suspected adverse drug reactions from healthcare professionals and patients and on the analysis of the quality of individual case safety reports sent from the marketing authorisation holders. During the training period I also had the opportunity to participate in some risk minimisation activities, such as the validation of direct healthcare professional communications. Besides the description of the activities and tasks performed over the period of the training, this report also describes the main difficulties encountered and the competencies that I believe I achieved during this professional experience. This training was my first contact with the work environment and gave me a clear perspective of how a Regional Pharmacovigilance Unit and a National Competent Authority work, as well as their interactions with the pharmaceutical industry, the healthcare professionals and the patients, allowing me, simultaneously, to acquire several competences at a personal and professional level, which will be essential for my future.